Integral definition and conceptual model of mental health: Proposal from a systematic review of different paradigms - Coronel-Santos, Maday Alicia; Rodríguez-Macías, Juan Carlos (Frontiers in Sociology, 2022)
Global society presents a mental health scenario characterized by the prevalence of mental disorders and the limited existence of formal care services. Faced with such a context, it is necessary to review what is understood and done in favor of mental health. This implies, in the first instance, analyzing the concept of mental health from a comprehensive approach that takes into account different perspectives from the social and natural sciences, related factors, and care options. Therefore, the present work aimed to propose an integral definition and a conceptual model of mental health based on the Systematic Literature Review, with the PRISMA approach, of the theoretical frameworks of 52 articles related to mental health published up to February 2022. A qualitative approach was used, with a Grounded Theory design, which allowed comparing different paradigms and identifying gaps in conceptual notions to build an explanatory model of mental health. The results showed three dominant paradigms that circumscribe the concept of mental health. Mental health is understood as the absence of illness, positive mental health, and a state of equilibrium. In addition, the need to propose a definition that integrates these dominant paradigms was mainly identified, and that would allow a broader understanding of the state of equilibrium as the basic process through which the individual must pass in the search for personal recovery. From the comparative analysis of the categories designated according to the Grounded Theory approach, an explanatory model was proposed to define mental health as the internal process of self-care, centered on the self-awareness and self-regulation of the human being, in which the person seeks to balance their feelings, thoughts, and behaviors, intrapersonal and interpersonal ones, to approach an optimal state of well-being and absence of mental disorders according to universal values and symptoms, and biological, social, psychological and environmental factors.